DOES COVID-19 INFLUENCE YOUNG GENERATIONâS STOCK INVESTMENT INTENTION IN EMERGING MARKET? - Aditya Nugraha, Bagus
Among numerous recent literatures in finance and investment, not yet been found any research that examines an individual's perceptive factors toward stock investment intention during the pandemic situation. Notably, in the scope of an emerging market. In Indonesia, the growth of investor numbers is relatively very small compared to the total population. This certainly reflects that Indonesian people's investment intention is very small as well. Notably, those young generations. Departing from this phenomenon, the author attempts to analyse several perspective factors of younger Indonesia generations toward stock investment intention during the pandemic. Because Indonesia has tremendous potential knowing that in the next few years, the current young generations will dominate the population structure. Henceforth, this recent research does not only aim to provide empirical evidence regarding the theory applicability that commonly used in analysing investment intention, but the author also aims to provide useful insights for all stakeholders involved in trying to increase young generations’ investment intention during today’s pandemic. Author utilise the perceptive variables from the Theory of Planned Behaviour (TPB) and various demographic characteristics as moderating variables. This current research conducted an online survey using a questionnaire to collect samples. 264 samples were collected and analysed using Partial Least Square methodology - Structural Equation Model and Multi-Group Analysis. Findings reveal that not all perceptive variables of TPB were found to be significant in the analysis of the young generations in Indonesia on stock investment intention; the only attitude toward behaviour had a significant effect. Besides, the level of education was found plays a moderating role in the relationship between young generations' perceptive variables and stock investment intention. Therefore, policymakers or other stakeholders can have a better understanding regarding recent young generations’ perspective on stock investment. Also able to know several possible actions that might be taken in terms of policies, programs, campaigns to increase the growth of investor numbers in Indonesia even during the pandemic situation. In the future, this research can be developed with a larger sample, more in-depth data collection techniques, and the addition of behavioural constructs that will make this research more comprehensive.